PENERAPAN PENDEKATAN TECHNOLOGICAL PEDAGOGICAL AND CONTENT KNOWLEDGE DALAM MENINGKATKAN MINAT DAN HASIL BELAJAR IPAS SISWA KELAS IV SEKOLAH DASAR - Nuril Hasbi, Ihza; Suswandari, Meidawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study focuses on the implementation of the Technological Pedagogical and Content Knowledge (TPACK) approach in IPAS learning (Integrated Science and Social Studies) as an effort to integrate IPAS content knowledge, pedagogical strategies, and the meaningful use of technology in students’ learning processes. The purpose of this study is to describe the application of the TPACK approach in increasing interest and learning outcomes of science in grade IV of Pranan 01 State Elementary School. This research employed a descriptive qualitative method involving one teacher and five students selected through purposive sampling technique. Data were collected through observation, in-depth interviews, and documentation, and then analyzed using the Miles and Huberman interactive model with the assistance of Nvivo software to identify patterns and relationships among the findings. The results of the study indicate that the integration of learning videos, interactive presentations, and guided discussions within the TPACK framework helps students become more focused, actively engaged, and able to understand concepts more clearly. These findings show that the TPACK approach plays an important role in supporting contextual and meaningful IPAS learning in elementary schools.